Organoleptic quality and TPC of smoked skipjack tuna (Katsuwonus pelamis, L) in Jayapura, Papua - Jeujanan, Samuel; Ijong, Frans G.; Onibala, Hens; Mentang, Feny (AQUATIC SCIENCE & MANAGEMENT, 2015)
Title (Bahasa Indonesia): Mutu organoleptik dan TPC ikan cakalang [Katsuwonus pelamis, L] asap di Kota Jayapura, Papua. This study was aimed at knowing the smoked skipjack tuna (Katsuwonus pelamis, L) marketed in JayapuraMunicipality. Sampling sites were Youtefa market and Hamadi market. The organoleptic paramters observed were appearance,smell, taste, texture, and Total Plate Count (TPC). The TPC analysis used a quantitative dispersion method. Results showed that different smoking duration and temperature, and the use of poor-quality used wood caused differences in organoleptic value. The highest organoleptic value was smell, (6.8) from Youtefa marketand the lowest was appearance (6) from Hamadi market). The TPC analysis revealed that the highest TPC was the samples from Youtefa market in February and March (4.1 x 105 and 3 x 105) followed by those from Hamadi market in February (4.8 x 105). The lowest TPC was recorded in April (3.7 x 103) in samples from Youtefa market and Hamadi market in March and April (4.7 x 104and 7.8 x 104). High contamination occurred at each processing phase to marketing. Penelitian ini bertujuan untuk melakukan kajian mutu ikan cakalang (Katsuwonus pelamis, L) asap yang dipasarkan di Kota Jayapura. Lokasi pengambilan sampel adalah Pasar Youtefa dan Pasar Hamadi. Mutu organoleptik yang diamati adalah kenampakan, bau, rasa, tekstur, dan mutu Total Plate Count (TPC). Analisis TPC menggunakan metode sebar yang bersifat kuantitatif. Hasil penelitian menunjukkan bahwa perbedaan lama waktu pengasapan, suhu, dan penggunaan kayu bekas yang kurang baik menyebabkan perbedaan nilai organoleptik. Nilai organoleptik tertinggi adalah bau dengan nilai 6,8 (Pasar Youtefa) dan terendah adalah kenampakan dengan nilai 6 (Pasar Hamadi). Hasil analisis TPC menunjukkan bahwa jumlah nilai TPC tertinggi adalah  sampel dari Pasar Youtefa pada bulan Februari dan Maret, (4,1x105 dan 3x105)  diikuti Pasar Hamadi pada bulan Februari (4,8x105). Kemudian perolehan nilai TPC terendah pada bulan April (3,7x103) di  Pasar Youtefa dan Pasar Hamadi bulan Maret dan April (4,7x104 dan 7,8x104). Tingginya kontaminasi terjadi pada setiap tahapan pengolahan sampai pada pemasaran.